THE ROLE OF FAMILY COMMUNICATION IN ADOLESCENT IDENTITY FORMATION IN THE MODERN ERA - Abdul Rosyad; Risqi Adi Kurniawan; Almaydza Pratama Abnisa (Sekolah TInggi Ilmu Dakwa dan Komunikasi Islam (STIDKIS) Al Mardliyyah Pamekasa, 2025)
Adolescents undergo a phase of identity exploration through social and family interactions. In Giwangretno Village, this process is influenced by modernization and digital media, which alter the dynamics of family communication. This study aims to explain the role of family communication and parental digital mediation in shaping adolescent identity in a modern rural environment. A qualitative approach was employed, utilizing observation, in-depth interviews, and documentation involving five adolescents, three parents, and two community figures. Data were analyzed using family communication theory and digital mediation theory. The findings indicate that family communication patterns in Giwangretno Village tend to be open and dialogical, allowing adolescents to express their opinions while fostering self-confidence and social responsibility. Family communication functions both as a means of instilling values and reinforcing emotional bonds. Parents implement three forms of digital mediation: restrictive, instructive, and participatory, with a dominance of the instructive pattern oriented toward education. This approach helps adolescents filter content, internalize positive values, and develop a reflective identity. The resulting adolescent identity is a hybrid of religious and modern values, harmoniously combining traditional values, religiosity, and digital modernity. Conclusion: Open family communication and instructive digital mediation strengthen a religious-modern adolescent identity and prevent identity crises in the digital era.